2020
DOI: 10.3389/fchem.2020.00696
|View full text |Cite
|
Sign up to set email alerts
|

Targeting L-Proline Uptake as New Strategy for Anti-chagas Drug Development

Abstract: L-Proline is an important amino acid for the pathogenic protists belonging to Trypanosoma and Leishmania genera. In Trypanosoma cruzi, the etiological agent of Chagas disease, this amino acid is involved in fundamental biological processes such as ATP production, differentiation of the insect and intracellular stages, the host cell infection and the resistance to a variety of stresses. In this study, we explore the L-Proline uptake as a chemotherapeutic target for T. cruzi. Novel inhibitors have been proposed … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Pidolic acid is an active form of 5-oxoproline and occurs in fundamental biological processes such as intracellular stage differentiation, host cell infection, and resistance to various stresses in protozoa belonging to the genera Trypanosoma and Leishmania . Fargnoli et al showed in an unprecedented way that l -proline uptake has been proposed as a chemotherapeutic target for Trypanosoma cruzi , opening a new horizon in the development of new chemotherapeutics against Chagas disease and other parasitic diseases ( 75 ).…”
Section: Discussionmentioning
confidence: 99%
“…Pidolic acid is an active form of 5-oxoproline and occurs in fundamental biological processes such as intracellular stage differentiation, host cell infection, and resistance to various stresses in protozoa belonging to the genera Trypanosoma and Leishmania . Fargnoli et al showed in an unprecedented way that l -proline uptake has been proposed as a chemotherapeutic target for Trypanosoma cruzi , opening a new horizon in the development of new chemotherapeutics against Chagas disease and other parasitic diseases ( 75 ).…”
Section: Discussionmentioning
confidence: 99%
“…5) was localized to the parasite cytoplasm in clusters resembling intra-organelle localization. The fact that the compound was indeed transported into the cell together with the proline uptake inhibition 22 , allowed us to postulate that: i. compound 1 (from which compound 4 is derived) could be competing with the amino acid incorporation, and ii. compound 1 has a different inhibition mechanism than 3.…”
Section: Discussionmentioning
confidence: 99%
“…As was mentioned, based on previous work 22,23 , proline analogues 1 -3 (Fig. 1) were selected for this study.…”
Section: Proline Analogues Are Active Against All T Cruzi Dtus (Tc I -Vi)mentioning
confidence: 99%
See 2 more Smart Citations